Carnosine Content and Its Association with Carnosine-Related Gene Expression in Breast Meat of Thai Native and Black-Bone Chicken - Khumpeerawat, Panuwat (Animals (Basel), 2021)
SIMPLE SUMMARY: Functional meat has become an important issue in the poultry industry because chicken meat is a rich source of carnosine. Additionally, carnosine synthesis is regulated by an ATP-grasp domain-containing protein 1 (CARNS1). However, no studies have elucidated the role of carnosine content and CARNS1 in Thai native and black-bone chicken. Thus, the aim of this study was to select and develop mating programs for functional meat in Thai chicken populations. Our results indicated that different breeds and ages of chickens have different amounts of carnosine and levels of CARNS1 expression. The carnosine content and CARNS1 expression decreased linearly as chicken age increased. Moreover, a moderate correlation was observed between carnosine content and CARNS1 expression levels. Therefore, the CARNS1 gene could be used to study marker assistant selection in the future. ABSTRACT: This study aimed to investigate the carnosine content and ATP-grasp domain-containing protein 1 (CARNS1) gene expression and their relationship with breast meat of Black Chinese (BC), KU-Phuparn (KP), Pradu Hang Dam (PD), and Black Chinese × Pradu Hang Dam (Sri Mok: SM) to aid in the selection and mating programs for developing functional meat in Thai chicken populations. The results show that the carnosine content in each breed and breed group varied from 428.08 to 553.93 mg/100 g, whereas the relative expression of CARNS1 ranged from 0.84 to 1.56. The BC and KP chicken breeds had a higher carnosine content (p < 0.01) and higher CARNS1 expression level (p < 0.05) than the SM and PD chicken breeds. The carnosine content and relative gene expression for each age ranged from 423.02 to 577.83 mg/100 g and 0.68 to 1.83, respectively. At 4 weeks of age, the carnosine content (p < 0.01) and gene expression (p < 0.05) were the highest. However, they decreased as chicken age increased further. The carnosine content and gene expression linearly decreased as chicken age increased (p < 0.01). The correlation coefficient between the level of gene expression and carnosine content was moderately positive. The results from this study showed that different breeds and ages of chickens have different amounts of carnosine, and CARNS1 could act as a biomarker to study marker-assisted selection to improve functional meat in the chicken population in Thailand.